Evaluation of Changes in Alveolar Bone Height Following Removable Orthodontic Appliances at Unimus Dental Hospital - Dea Zahra Khairunnisa; Dimar Pangestika Sari; Ayuda Nur Sukmawati; M. Al Haris (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2026)
Introduction: Malocclusion is a condition characterized by misalignment of the teeth and improper jaw alignment, which can lead to impaired chewing function. One type of orthodontic appliance that can be used in the treatment of malocclusion is the removable orthodontic appliance. This appliance offers the advantage of being easily removed and reinserted by the patient, thereby helping to maintain better oral hygiene, and carries a lower risk of root resorption and periodontal complications compared to fixed orthodontic appliances. Research on changes in alveolar bone height has largely focused on the use of fixed orthodontic appliances, while studies on removable orthodontic appliances remain limited. Aim: This study aims to evaluate the differences in alveolar bone height before and after the use of removable orthodontic appliances in patients at Unimus Dental Hospital. Methods: This study applied an analytical observational approach with a cross-sectional design. The study was conducted by measuring the alveolar bone height on panoramic radiographs before and after the use of removable orthodontic appliances on 10 teeth in 17 subjects using ImageJ® software. Result: The results of both the paired sample t-test and the Wilcoxon signed rank tests showed p-values greater than 0.05. Conclusion: There was no difference in alveolar bone height before and after the use of removable orthodontic appliances in patients at the Unimus Dental Hospital Keywords: alveolar bone, bone resorption, removable orthodontic appliances